Microsoft SQL Server high availability - Bertucci, Paul (Microsoft Windows server system series., 2005)
Explains how to assess, select, and build high availability solutions from the ground up. Learn valuable skills, including how to drill down into the heart of high availablity requirements, and how to assess and classify these requirements, and how to select, configure, and specify a matching high availability solution that optimally meets your needs.